Effect of genotype on herbivory and growth rate in Heliconia stricta in a common garden experiment in the Amazon - Xaali O’REILLY-BERKELEY; Abhiraj CHAKRABORTY; Javier L. PATIÑO UYAGUARI; Hannah L. MOSSMAN; Richard F. PREZIOSI; Jennifer K. ROWNTREE (Acta Amazonica)
ABSTRACT Plant genotype is known to affect plant-invertebrate interactions. However, in megadiverse tropical habitats there has been relatively little exploration of the influence of the plant genotype on plant growth and biotic interactions in an experimental setting. We set-up three adjacent plots in rainforest at the foothills of the Andes (Orellana, Ecuador), where we planted clones of 37 individual Heliconia stricta rhizomes collected from up to 4 km away. Each rhizome was split into at least three individual pieces, resulting in three genetically identical replicates. At least one representative of each genotype was planted in each plot. Shoot height was measured every few months. Nine months after planting, all leaves of the plants were photographed for leaf herbivory analysis. At the time of the herbivory analysis, neither shoot height nor total leaf area were more variable among than within genotypes, but the total percentage of leaf area consumed per plant varied significantly among the genotypes. Whether or not there was a significant difference in shoot height among genotypes depended on the timepoint at which the plants were measured. However, the overall growth rate over a period of 1.5 years varied significantly among the genotypes. Our results suggest that even in megadiverse systems and despite the plasticity of plant responses, plant genotype can influence growth rate and biotic interactions such as herbivory.